The Impact of Person-Organization Fit and Person-Job Fit on Employee Performance Through Affective Commitment - Umu Faza Kurnia; Prasojo Hendiwinisudo (Universitas 17 Agustus 1945 Semarang, 2026)
This study aims to analyze the effect of person–organization fit and person–job fit on employee performance, with affective commitment as an intervening variable. The study employs a quantitative approach using a survey method by distributing questionnaires to employees, and the data are analyzed using SEM-PLS to examine the relationships among variables. The results indicate that person–organization fit and person–job fit have a positive and significant effect on employee performance. Furthermore, affective commitment is proven to have a positive and significant effect on employee performance and is able to mediate the relationship between person–organization fit, person–job fit, and employee performance. These findings emphasize the importance of alignment between individual values, job characteristics, and emotional attachment in enhancing employee performance in public sector organizations.